Analisis Permasalahan Pembelajaran PPKn Objek Kajian Di SMA Negeri 18 Medan - Adelina Marta Aritonang; Iwain Oktaviona Nababan; Victoria Grace Daely; Putri Permata Assiddiq Harahap; Fariz Aditya; Samuel Sihite (LPPM Politeknik Pratama, 2023)
PPKN occupies a very strategic position in forming the character of Indonesian citizens. So we can find this subject at all levels of education. This research aims to analyze problems in PPKN learning at SMA Negeri 18 Medan. The focus of this research includes issues of learning methods, learning resources, learning media and the results of PPKn learning scores. The research method used is a descriptive qualitative research method, used as a guide so that the research focus is in accordance with the facts in the field. The results of this research show common problems in Civics learning, such as a curriculum that is constantly changing and too heavy, the use of monotonous lecture methods, limited learning resources and a lack of use of learning media. Based on these problems, the aim of writing this journal is to explain several problems that occur in PPKn learning at State High School 18 Medan and how to overcome the problems faced in PPKN learning in the current era of the independent curriculum